2013
DOI: 10.1371/journal.pntd.0002034
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Infection and Endothelin-1 Cooperatively Activate Pathogenic Inflammatory Pathways in Cardiomyocytes

Abstract: Trypanosoma cruzi, the causative agent of Chagas' disease, induces multiple responses in the heart, a critical organ of infection and pathology in the host. Among diverse factors, eicosanoids and the vasoactive peptide endothelin-1 (ET-1) have been implicated in the pathogenesis of chronic chagasic cardiomyopathy. In the present study, we found that T. cruzi infection in mice induces myocardial gene expression of cyclooxygenase-2 (Cox2) and thromboxane synthase (Tbxas1) as well as endothelin-1 (Edn1) and atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 61 publications
(93 reference statements)
1
40
0
Order By: Relevance
“…RAGE ligands (e.g., endogenous alarmin S100 proteins) have been shown to increase Cox2 expression in RAGE-related inflammatory settings (43). In parasitic diseases, COX2 has also been shown to be upregulated and predicted to have an impact (44). On the other hand, MCP-5, known as an MCP-1-related chemokine, specifically attracts monocytes and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE ligands (e.g., endogenous alarmin S100 proteins) have been shown to increase Cox2 expression in RAGE-related inflammatory settings (43). In parasitic diseases, COX2 has also been shown to be upregulated and predicted to have an impact (44). On the other hand, MCP-5, known as an MCP-1-related chemokine, specifically attracts monocytes and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, we previously found that T. cruzi infection and endothelin-1 (ET-1) cooperatively activate the Ca 2+ /calcineurin/NFAT cascade in atrial myocytes, leading to cyclooxygenase type 2 (COX-2) induction and increased release of inflammatory mediators (Corral et al, 2013). As the antiinflammatory actions of Cur largely stem from its ability to target key molecules (enzymes, cytokines, transcription factors) implicated in the etiology of different malignancies (Deguchi, 2015), we aimed to investigate whether Cur treatment of ET-1-stimulated and T. cruzi-infected cardiac cells could interfere with this pathway responsible for the production of inflammatory effectors relevant to the pathogenesis of Chagas heart disease.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…Mouse HL-1 cardiomyocytes were plated onto gelatin/fibronectin precoated flasks and cultured at 37ºC, 5% CO 2 in Claycomb medium (SigmaAldrich) supplemented with 10% fetal calf serum (FCS), 100 U/ml penicillin, 100 μg/ml streptomycin and 2 mM L-glutamine as previously described (Corral et al, 2013). HL-1 cells were treated with 0.3 nM endotoxin-free ET-1 (Sigma-Aldrich) for 2 h and then infected for 3 h or 24 h with T. cruzi trypomastigotes (cell:parasite ratio 1:5), RA strain, in the presence and absence of Cur (0-13.5-27.0 μM).…”
Section: Cell Culture Primary Cardiomyocytes and Infectionmentioning
confidence: 99%
“…Although T. cruzi trypomastigotes are broadly dispersed among many different organs in the mammalian host, cardiac tissue is an important target for this parasite, and the T. cruzicardiomyocyte interaction has been the subject of intense investigation (4)(5)(6)(7).…”
mentioning
confidence: 99%